An elastic caterpillar-based self-propelled robotic colonoscope with high safety and mobility. (November 2016) - Lee, Dongkyu; Joe, Seonggun; Choi, Junwoo; Lee, Bo-In; Kim, Byungkyu
Abstract: Colonoscopies are one of the best methods of screening colorectal cancer (CRC) at present. Since conventional colonoscopes have some drawbacks concerning diagnostic procedures, robotic colonoscopes have been studied for smooth intubation. However, previously developed robotic colonoscopes still suffer from disadvantages such as poor locomotion performance and the occurrence of local bleeding due to harsh clamping. In a previous study, therefore, we presented an elastic caterpillar-based robotic colonoscope actuated by an external motor through a flexible shaft to enhance safety and mobility. However, in-depth discussion was not included on theoretical and experimental evaluations for the design of each component. Moreover, the only demonstration of the design's feasibility was carried out without a steering module. Therefore, in the present study, theoretical and experimental evaluations are provided so as to select the optimal components for the robot to guarantee safety, steerability, and mobility. Based on these theoretical and experimental results, the proper components are fabricated and assembled into a robotic colonoscope. Subsequently, a mobility test is performed in an excised porcine colon. The robotic colonoscope shows reliable locomotion performance; it has forward and backward velocities of 5.0 ± 0.4 mm/s and 9.5 ± 0.9 mm/s, respectively. When facing inclined angles of 30˚ and 60˚, the robot moves forward at velocities of 6.1 ± 1.1 mm/s and 4.7 ± 0.7 mm/s, respectively. Furthermore, in order to confirm the feasibility of locomotion performance in a human colon, an additional locomotion test is performed with a lower gastrointestinal phantom mimicking a human colon. Here again, the robot shows high locomotive performance with a velocity of 3.0 ± 0.2 mm/s. Finally, to validate the feasibility of a clinical demonstration for the robotic colonoscope, an in-vivo test is implemented with a live mini pig. Conclusively, owing to a reliable mechanism and a steering module, the robot shows reliable locomotion without complications such as bleeding or perforations in the colon.